Penundaan Makanan Padat Mengurangi Risiko Timbulnya Atopi pada Anak - Barlianto, Wisnu; Kusuma, HMS Chandra; HM, Ni Luh Putu (Fakultas Kedokteran Universitas Brawijaya, 2009)
Nutritions plays an important role in the incidence of atopic both in children and adults. Several recent guidelines recommend a delay of solid foods to prevent atopic disease. However, until now, there is still much controversy about the influence a delay of solid foods in children to develop atopic disease. This study aimed to determine the impact of the start time of solid foods to atopic children. A case-control study was conducted in outpatient institutions Pediatrics RSSA Malang from May 2008 until May 2009. Respondents were divided into two groups: atopic (cases) and non atopic (control) based on history of atopic disease. The age of first given solid food and familial atopic were retrieved based on history . Statistical analysis using Chi-square test at 95% level of confidence, was conducted to determine the impact of the start time of solid food to the incidence of atopic. There were 236 patients divided equally into atopic and control group. Giving solid foods at 4-6 months of age will increase the risk of atopic compared with age> 6 months (OR 2.8 (1.29 to 6.07), p = 0.007). The results of this study support the recommendations given by WHO, that the postponement of solid food until age 6 months would reduce the incidence of atopic risk in children.Keywords : postponement , solid food, atopic diseases, sensitization